The Relationship between Emotional Violence and Learning Achievement of Female Students - Reski Aulia; Suci Musvita Ayu (Intelektual Pustaka Media Utama, 2015)
Violence is a phenomenon social happened and inclined for women as a sacrifice. There are still a few people who know the violence that is happened in relationship. It is because they assume that relationship is amazing time in young age. It is one of ignorance from citizens that they are less of information and data report of violence victim in the relationship. Learning achievement is measured of the success of students in learning activities. Influence factors achievement of study can be classified into two groups, namely the internal self sourced from students and external factors included factors of family, school and community environment factors. The aim of the research was to investigate the relationship between emotional violence and learning achievement of female students in SMK Negeri 6 Yogyakarta, Indonesia. This study was observational analytic employing cross sectional design. The subject of research was 85 students of SMK Negeri 6 Yogyakarta. The results showed that there was no relationship between emotional violence with learning achievement.